Epidemiology of sepsis and risk factors for mortality in intensive care unit: a hospital based prospective study in South India. Issue 5 (4th May 2022) - Garg, Rahul; Tellapragada, Chaitanya; Shaw, Tushar; Eshwara, Vandana Kalwaje; Shanbhag, Vishal; Rao, Shwethapriya; Virk, Harjeet S.; Varma, Muralidhar; Mukhopadhyay, Chiranjay
Abstract: Objective: The present study was aimed at elucidating the epidemiology of sepsis, with a special emphasis on identifying the common bacterial aetiology, proportion of infections caused by multi-drug resistant (MDR) bacteria, and risk factors associated with 28-day mortality at a university hospital in South India. Methods: A prospective study was undertaken from January 2017 to March 2018. Adult patients with the diagnosis of sepsis requiring intensive care unit (ICU) care were recruited. Baseline clinical, epidemiological, and laboratory data were recorded, and their association with 28-day mortality was assessed using logistic regression models. Results: 400 subjects with a qSOFA score ≥2 at the time of ICU admission were included in the study. The mean age was 55.7 ± 16.6 years, and 69% were males. The mean SOFA score at the time of admission was 9.9 ± 2.7. Bacterial aetiology of sepsis was established in 53.5% of cases and 24% were caused by MDR pathogens. Carbapenem resistance was observed in 37% of the Gram-negative isolates. Escherichia coli (34.1%) was the leading pathogen. Overall, the 28-day mortality in ICU was 40%. 38% died within 48 h of ICU admission. Hypertension and SOFA > 9, male gender, and baseline-creatinine values >2.4 mg/dl were risk factors for mortality. Conclusions: Male gender, hypertension, SOFA > 9, and increased creatinine were identified as the predictors for mortality. Infectious aetiology remained undetected in nearly half of the cases using routine microbiology culture methods. Mortality within the first 48 h of admission to ICU is high and prompts the need for increasing awareness about early sepsis diagnosis in community health care settings.